A comparative study to evaluate the corrosion performance of Zr incorporated Cr3C2-(NiCr) coating at 900 °C. Issue 6 (15th April 2018) - Ahuja, Lalit; Mudgal, Deepa; Singh, Surendra; Prakash, Satya
Abstract: In this study zirconium incorporated Cr3 C2 -(NiCr) coating has been sprayed on three superalloys viz. Superni 718, Superni 600 and Superco 605 using D-gun technique. A comparative study has been carried out to check the cyclic oxidation in air and hot corrosion in simulated incinerator environment (40%Na2 SO4 -40%K2 SO4 -10%NaCl-10%KCl) for the coated specimens at 900 °C for 100 cycles. Oxidation kinetics has been established for all the specimens using weight change measurements. Corrosion products have been characterized using X-ray diffractometer (XRD) and scanning electron microscopy/energy-dispersive analysis (SEM/EDAX). Cr3 C2 -(NiCr) + 0.2%wtZr coating provides very good corrosion resistance in air oxidation for all the three coated superalloys. As all the three coated superalloys shows parabolic behaviour with parabolic rate constant as 0.07 × 10 −10 (g 2  cm −4  s −1 ) for Superni 718, 0.43 × 10 −10 (g 2  cm −4  s −1 ) for Superni 600 and 0.3 × 10 −10 (g 2  cm −4  s −1 ) for Superco 605 This coating is also effective in the molten salt environment but coating on Co-based superalloy Superco 605 did not perform satisfactorily. The parabolic rate constants for coated Superni 718 is 0.61 × 10 −10 (g 2  cm −4  s −1 ), for coated Superni 600 is 6.72 × 10 −10 (g 2  cm −4  s −1 ) and for coated Superco 605 is 17.5 × 10 −10 (g 2  cm −4  s −1 ).